Biosensors for measuring nitric oxide NO levels in biosubstrates: a systematic analysis - I. Yu. Torshin; O. A. Gromova; L. A. Mayorova; A. N. Gromov (Фармакоэкономика, 2023)
Nitric oxide NO is a signaling molecule involved in numerous physical and pathological processes in biological systems. Highly sensitive sensor materials for measuring NO amounts in vivo in exhaled air and in body fluids (saliva, blood, urine) can be a useful tool in diagnostics and management of patients with bronchopulmonary, cardiovascular, neurological and tumor diseases. Several approaches to measuring NO in biosubstrates (including exhaled air) have been developed: fluorescence/chemiluminescence, electron spin resonance, electrochemical/amperometric (organic and inorganic) and enzymatic/protein sensors. Semiconductors, transition metal nitrides, phthalocyanine complexes, porphyrin and cobalamin derivatives with metals can serve as materials for NO sensors. Creating sensor materials based on vitamin B12 derivatives is an urgent research task in biomedicine. The article systematizes information on using various compounds as materials for NO-sensitive and selective sensors to measure/evaluate NO levels in various biosubstrates.